"Muddling through": the dynamics of talent development in Norwegian women's handball - Bjørndal, C. T. (NIH, 2017)
This thesis reports on talent development in Norwegian handball. The literature on elite sports describes normative systems that should be used for talent identification and development but which do not resemble the actual workings of Norwegian handball. Studies of athletic development have traditionally focused on development as an individual enterprise within physiological or psychological frameworks. Far less attention has been given to how development and performance are embedded within an organisational setting. The overall aim of this study is therefore to investigate how the organisational context of Norwegian handball shapes and influences youth national team athletes` experiences and development. The research was conducted as an embedded case study, the purpose of which was to describe and examine individual development processes within Norwegian handball through four related empirical studies. The objective of the first study was to describe how talent development is organised in Norwegian handball, to identify how inherent organisational characteristics influence talent development processes, and to consider if contemporary normative talent development models provide an adequate conceptualisation of the actual model applied in Norwegian handball. In the second study, the aim was to investigate youth national team players` experiences of their developmental processes. Using a longitudinal design, the third study aimed to examine individual pathways to the adult elite level among a group of players with youth national team experience. Finally, the aim of the fourth study was to investigate the successful and unsuccessful transitions to the elite level made by a group of nine youth national team players. The findings from this study showed that the talent development model in Norwegian handball is heterarchical and consists of multiple key actors, namely: local clubs; sport schools; and regional and national athlete development initiatives provided by the Norwegian Handball Federation, hereunder referred to as the youth national teams. In this model, no organisational actor has the main responsibility for talent development, and no actor has any instructional authority over others. Successful athlete development is not only dependent on the individual significance of each actor but in how well each actor complements the others. The organisational context of Norwegian handball creates multiple possible pathways to the adult elite level. Individual development was found to be nonlinear, and individuals varied both in terms of the number and nature of the activities undertaken, the sequence of activities, and the time athletes spent at different and multiple practice settings and competition levels over the course of their development. The costs of coordination are high within multi-centric systems. Unintended consequences arise, both positive and negative: incidents and decisions beyond an athlete`s immediate context can facilitate or inhibit successful transitions to the adult elite level. The application of the talent development model used in Norwegian handball is frequently experienced as one which is exhausting for athletes. This research has practical implications: those involved in talent development within heterarchical and multi-centric organisational settings must recognise the simultaneous, socially-situated and complex processes involved, and how these affect planning, monitoring, and coordination. Addressing the increased coordination challenges of talent development in Norwegian handball requires continuous attention to the mundane activities of athlete development across team settings. Effectively planning and coaching for talent development therefore becomes an act of noticing the changing needs of athletes, where strategies must be flexible and requires mutual adaption.